Tourism Development based on Local Wisdom Through the Implementation of CHSE and CPR Adaptations in Tourism Destinations - Purnama, Ita; Fitriani, Fani (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Tourism has experienced a crisis in the form of a lack of trust in destinations since the pandemic period some time ago until now, so a strategy is needed to restore tourist trust, one of which is by developing a Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) protocol. Apart from that, the implementation of Cyber ​​Public Relations (CPR) is a public relations initiative that uses internet media as a means of publicity. This type of research is associative research which is to determine the cause and effect of a relationship between two or more variables. The population used in this research is all visitors to tourist destinations in Bima city with unknown numbers (unknown population) where the sample used is 180 respondents by using a sampling technique. The sampling technique is purposive sampling. Data collection techniques are through observation, questionnaires, and literature study using data analysis techniques that are validity test, reliability test, classical assumption test, multiple linear regression test, determination and correlation, t-test, and f test. The results of research carried out by researchers are 1) CHSE (X1) has a significant effect on tourism development with a t-count value of 3,579 > t-table of 2,007 with a significance value of 0,001 < 0,05, 2) CPR (X2) has a significant effect to tourism development with a t-count value of 3,439 > t-table of 2,007 with a significance value of 0,001 < 0,05, 3) CHSE and CPR have a simultaneous effect on tourism development at tourist destinations in Bima city with an f-count of 23,273 > f-table is 3,18 with a significance of 0,000 < 0,05.